Reinterpretation of Marriage Registration in Indonesian Islamic Family Law: From Fiqh Formalism to Legal Protection - Bangkit Satriya; Deni Kurnia; Irsadunas Noveri; Siti Marlina (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
The practice of unregistered marriage remains a significant issue within Indonesian Islamic family law due to its implications for women’s protection children’s legal status inheritance rights legal identity access to public services and the legal certainty of Muslim families This condition reflects a persistent tension between legal formalism in classical fiqh which primarily emphasizes the fulfillment of normative marital requirements and the contemporary need for legal protection within modern administrative and digital governance systems This study aims to reinterpret marriage registration within the framework of Indonesian Islamic family law reform by shifting its meaning from a merely legal-administrative formality toward substantive legal protection The research employs a critical normative legal method using socio-legal conceptual statute and maqashid syariah approaches to examine the relationship between classical Islamic jurisprudence Indonesian positive law and the evolving demands of legal protection in contemporary Muslim society The novelty of this study lies in its reconstruction of marriage registration as an instrument of legal protection rather than a purely administrative obligation within modern Islamic family law systems The findings demonstrate that the development of modern state administration digital governance and integrated civil registration systems has transformed marriage registration into a substantive legal protection mechanism closely connected to hifzu al nasal and hifzu al huquq the protection of women and children legal identity and the legal certainty of Muslim families This article contributes to the reform of Indonesian Islamic family law the reinterpretation of contemporary Islamic legal thought based on maqashid syariah and the advancement of socio-legal studies within modern Islamic family law scholarship